2015
DOI: 10.1016/j.taap.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Lipid rafts regulate PCB153-induced disruption of occludin and brain endothelial barrier function through protein phosphatase 2A and matrix metalloproteinase-2

Abstract: Occludin is an essential integral transmembrane protein regulating tight junction (TJ) integrity in brain endothelial cells. Phosphorylation of occludin is associated with its localization to TJ sites and incorporation into intact TJ assembly. The present study is focused on the role of lipid rafts in polychlorinated biphenyl (PCB)-induced disruption of occludin and endothelial barrier function. Exposure of human brain endothelial cells to 2,2′,4,4′,5,5′-hexachlorobiphenyl (PCB153) induced dephosphorylation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 68 publications
2
7
0
Order By: Relevance
“…MMP-2/9 specifically are gelatinases that activate pro-inflammatory agents and mediate TJ protein degradation [ 66 , 67 ]. Our observations are in agreement with the involvement of MMPs in the regulation of tissue barrier integrity as shown previously by us [ 68 ] and others [ 69 ]. ß-catenin has been linked to MMP-2/9 in epithelial cells via negative regulation as inhibition of Wnt/ß-catenin signaling led to increases in extracellular matrix metalloproteinase inducer (EMMPRIN) and MMP-2/9.…”
Section: Discussionsupporting
confidence: 94%
“…MMP-2/9 specifically are gelatinases that activate pro-inflammatory agents and mediate TJ protein degradation [ 66 , 67 ]. Our observations are in agreement with the involvement of MMPs in the regulation of tissue barrier integrity as shown previously by us [ 68 ] and others [ 69 ]. ß-catenin has been linked to MMP-2/9 in epithelial cells via negative regulation as inhibition of Wnt/ß-catenin signaling led to increases in extracellular matrix metalloproteinase inducer (EMMPRIN) and MMP-2/9.…”
Section: Discussionsupporting
confidence: 94%
“…MMP-2/9 specifically are gelatinases that activate proinflammatory agents and mediate TJ protein degradation 62,63 . Our observations are in agreement with the involvement of MMPs in the regulation of tissue barrier integrity as shown previously by us 64 and others 65 . ß-catenin has been linked to MMP-2/9 in epithelial cells via negative regulation as inhibition of Wnt/ß-catenin signaling led to increases in EMMPRIN, an extracellular MMP inducer, and MMP-2/9.…”
Section: Discussionsupporting
confidence: 94%
“…The calcineurin-dependent dephosphorylation of TRPV1 [37] and the PIP 2 depletion from the membrane [35] was proposed as mechanisms of the desensitization. Considering that the calcineurin was predominantly present in non-lipid raft domains [38], the present results propose a hypothesis that the membrane domain localization of TRPV1 spatially controls the balance between the Ca 2+ -dependent phosphorylation and dephosphorylation. The VB-HMM analysis suggested that TRPV1 molecules are in dynamic transition among three diffusion states with subsecond time constants (Figure S15).…”
Section: Discussionmentioning
confidence: 66%